Factors influencing unemployment among fresh graduates in Malaysia / Ayu Adirah Zamri, Nisa' Nabilah Abdul Jamil and Jannatul Farhana Rahman - Zamri, Ayu Adirah; Abdul Jamil, Nisa' Nabilah; Rahman, Jannatul Farhana (2019)
The increasing number of unemployment among graduates is one of the issues that captures everyone's attention. Consequently, this research aims to identify the significant factors influencing unemployment among fresh graduates in Malaysia from three aspects, which are Graduate's Attributes, Employability Skills and Job Mismatch. A total of 200 Malaysian fresh graduates were involved in the study and the data were analyzed using Multiple Linear Regression analysis. The researcher uses questionnaire that was adopted as the method to collect all the data from sample respondents in accomplishing the research objectives. The result showed that Graduate's Attributes and Job Mismatch have influence on unemployment among fresh graduates in Malaysia while Employability Skills did not give any significant influence on unemployment. All significant variables show positive relationship towards the unemployment among graduates. The study revealed that the fresh graduates need to adopt more employability skills and equip themselves with more appropriate knowledge as required by the industry. The study can be seen as forward to a more detailed study to be carrying by future research on the issue of unemployment among fresh graduates in Malaysia.